MODERN APPROACHES TO ASSESSING THE TECHNICAL AND TACTICAL SKILLS OF ATHLETES IN MIXED MARTIAL ARTS - Radchenko, Yu. A.; Dovhaninets, O. L.; Radchenko, A. A. (Rehabilitation and Recreation, 2025)
Introduction. In modern scientific publications devoted to various aspects of athletes’ fitness, more and more attention is paid to finding new ways to increase the effectiveness of athletes’ technical and tactical skills and creating prerequisites for optimizing the process of sports training and participation in competitions.The aim of the study to identify the most important characteristics that reflect a certain aspect of the technical and tactical skills of athletes in mixed martial arts.Research methods: theoretical analysis and generalization of literary sources; questionnaires, pedagogical observation, qualimetry, methods of mathematical statistics.Results. During this study, thanks to experts, it was possible to identify the most important factors that are important for determining the main components that would reflect the most significant aspects of the technical and tactical skills of mixed martial arts fighters.During the work, 25 initial indicators were identified that reflected the most significant aspects of the technical and tactical skills of athletes. The application of the principal component analysis method allowed us to reduce the number of indicators studied and highlight the most informative factors that affect technical and tactical skills. Based on these components, taking into account their substantive meaning and connection with the initial indicators, we proposed criteria for assessing the technical and tactical skills of athletes.The study made it possible to understand what exactly these generalized criteria reflect — characteristics that reflect a certain aspect of the technical and tactical skills of athletes and how they can be used in the practical activities of coaches.Conclusions. It has been established that the technical and tactical skill of martial artists depends on a complex of factors that differently affect the successful performance of technical and tactical actions and victory in a competitive duel. The four main factors that were identified in the course of the work retain a significant part of the information about the original 25 indicators and explain 88.32% of the total variance.